18S rRNA Metagenomic Analysis of Nodular Gill Disease in Swiss Rainbow Trout (Oncorhynchus mykiss) - Wynne, James W (Journal of fish diseases, 2025)
© 2024 The Author(s). Journal of Fish Diseases published by John Wiley & Sons Ltd.